2016
DOI: 10.12973/edupij.2016.52.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Loneliness and Depression: Mediation Role of Internet Addiction

Abstract: The aim of this study is to examine the mediation role of internet addiction in the relationship between loneliness and depression. 452 university students (241 women, 211 men) ranging in age from 17 to 31 and who are receiving education in different faculties at Firat University in Turkey participated in the study. UCLA Loneliness Scale, Young Internet Addiction Test Short Form, and Indication Scanning List was applied to the participants. The data were analyzed with correlation, regression, hierarchical regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
2
29
0
4
Order By: Relevance
“…Many prior studies mainly explored the relationship between internet addiction and depression, anxiety, stress, loneliness, self-esteem, social connectedness, insomnia, and other variables related to mental health issues (Akin & İskender, 2011;Cheung & Wong, 2011;Demir, 2016;Ha et al, 2007;Kim et al, 2006;Kimberly, 1998;Savci & Aysan, 2017;Selfhout et al, 2009). Nearly all these studies found a positive relationship between internet addiction and depression and other variables relevant to mental health; however, an earlier study of (Shaw & Gant, 2002) found a negative relation between internet addiction and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies mainly explored the relationship between internet addiction and depression, anxiety, stress, loneliness, self-esteem, social connectedness, insomnia, and other variables related to mental health issues (Akin & İskender, 2011;Cheung & Wong, 2011;Demir, 2016;Ha et al, 2007;Kim et al, 2006;Kimberly, 1998;Savci & Aysan, 2017;Selfhout et al, 2009). Nearly all these studies found a positive relationship between internet addiction and depression and other variables relevant to mental health; however, an earlier study of (Shaw & Gant, 2002) found a negative relation between internet addiction and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when the effects of technological addictions on social connectedness are examined, it is necessary to take personality traits into account. Hence, it has been found in research that technological addictions are closely related to personality traits (90)(91)(92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, researchers believe that loneliness is a crucial factor when considering Internet addiction ( Morahan-Martin and Schumacher, 2003 ; Manouchehr et al, 2007 ; Song et al, 2014 ; Demir and Kutlu, 2016 ). Three relevant theories exist: Internet addiction leads to loneliness, loneliness leads to Internet addiction, or loneliness and Internet addiction interact with each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second view suggests that lonely people are more likely to be attracted to Internet use ( Morahan-Martin and Schumacher, 2003 ; Özdemir et al, 2014 ; Song et al, 2014 ; Demir and Kutlu, 2016 ; Sharifpoor et al, 2017 ). Excessive Internet use occurs because the Internet provides a wider social network and a variety of online forms of communication.…”
Section: Literature Reviewmentioning
confidence: 99%